2019
DOI: 10.1002/pc.25410
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic carbon nitride (g‐C3N4) reinforced polymer nanocomposite systems—A review

Abstract: Research on polymer matrix-enhancement using a carbon nanomaterial as the highpotential filler has attracted considerable attention to meet the increasing demand for advanced polymer composites which show promising applications in a wide variety of fields. Graphitic carbon nitride (g-C 3 N 4 ) is the most stable allotrope of carbon nitrides and its inherent electron-rich properties, basic surface functionalities, and hydrogen bond motifs make it a potential candidate in catalysis and in other fields. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 93 publications
(88 reference statements)
0
33
0
Order By: Relevance
“…Another class of nanostructured epoxies, i.e., the organic–inorganic hybrid one, is introduced, highlighting its strong potential in many applications. Differently from other recent reviews focused on specific properties of the nanocomposites [ 7 , 8 , 9 , 10 ] or individual nanoparticles [ 11 , 12 , 13 ] added to epoxy, a wide-ranging overview of many characteristics and nanofillers has been presented in this paper. The different methods and routes employed to produce nanofilled/nanostructured epoxies are then described.…”
Section: Introductionmentioning
confidence: 99%
“…Another class of nanostructured epoxies, i.e., the organic–inorganic hybrid one, is introduced, highlighting its strong potential in many applications. Differently from other recent reviews focused on specific properties of the nanocomposites [ 7 , 8 , 9 , 10 ] or individual nanoparticles [ 11 , 12 , 13 ] added to epoxy, a wide-ranging overview of many characteristics and nanofillers has been presented in this paper. The different methods and routes employed to produce nanofilled/nanostructured epoxies are then described.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that filling g-C 3 N 4 improves the tribological properties of PPESK. As a result, an excellent self-lubricating property is achieved because of its interlayer bonding through van der Waals forces [40]. On the other hand, the friction coefficient and wear rate of g-C 3 N 4 /Ag-PPESK are not only much lower than those of PPESK, but also are lower than those of g-C 3 N 4 reinforced PPESK composite film.…”
Section: Thermal Properties Of Ppesk Composite Film With G-c 3 N 4 /Agmentioning
confidence: 99%
“…Either of the two could be combined with other semiconductors to degrade organochlorine pesticides with improved degradation efficiency [130,132]. The improved efficiency could be attributed to better light absorption, narrowed band gap, limited recombination of charge carrier and improved separation of charge carrier [133]. Graphitic oxide and graphene oxide have been used to degrade 4-chlorophenol in water.…”
Section: Graphene Oxide-based Photocatalyst For Pesticide Degradationmentioning
confidence: 99%